Conjugation of a photosensitizer to near infrared light renewable persistent luminescence nanoparticles for photodynamic therapy. Issue 90 (26th October 2016) - Abdurahman, Renagul; Yang, Cheng-Xiong; Yan, Xiu-Ping
Abstract : A photosensitizer is conjugated to near infrared light renewable persistent luminescence nanoparticles for photodynamic therapy without continuous external irradiation. Abstract : We report 808 nm NIR light renewable NIR persistent luminescence sensitized photodynamic therapy (PDT). Persistent luminescence provides an internal light source to generate singlet oxygen for PDT. This work paves the way for the next generation of PDT without any need for continuous external light irradiation.